INFRARED SPECTROMETRY IN DIAGNOSTICS OF THE UTERINE CERVIX - L. V. Borovkova; E. V. Ionova; O. V. Kachalina; D. V. Pershin; A. A. Ignatyev (Акушерство, гинекология и репродукция, 2016)
There was carried out the spectrometric examination of blood serum of women with benign and neoplas- tic diseases of uterine cervix; the diagnosis was histologically verified. Being minimally invasive method, infrared spectrometry has proved high specificity and sensitivity in comparison with standard examination methods and it has to find wide usage in obstetrician-gynecologist’s every day practice.